Gradient transition composite tantalum carbide coating and preparation method thereof

By depositing a gradient transition composite tantalum carbide coating on the graphite matrix, the problem of the coating being prone to cracking is solved, and process control is simplified, improving the thermal shock resistance and adhesion of the coating.

CN119710620APending Publication Date: 2025-03-28SHANDONG GUOJING NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411971523.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the difference in thermal expansion coefficient between the tantalum carbide coating and the graphite matrix causes the coating to crack easily and affect performance. At the same time, the multi-component CVD co-deposition process is complex, the component control is difficult, and the process parameter optimization is time-consuming and costly.

Method used

The gradient transition composite tantalum carbide coating is prepared by high-temperature chemical vapor deposition method. The coating consists of a pyrolytic carbon coating, a tantalum carbide-pyrolytic carbon composite coating and a tantalum carbide coating. The difference in thermal expansion coefficients is alleviated through the gradient transition structure, and the process parameter optimization is simplified by controlling the gas flow and temperature during the deposition process.

Benefits of technology

It effectively improves the adhesion between the coating and the substrate, alleviates the cracking problem caused by the difference in thermal expansion coefficient, improves thermal shock resistance, simplifies process control, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710620A_ABST
    Figure CN119710620A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductors, and particularly relates to a gradient transition composite tantalum carbide coating and a preparation method thereof.The gradient transition composite tantalum carbide coating is located on the surface of a graphite substrate material and sequentially comprises a pyrolytic carbon coating, a tantalum carbide-pyrolytic carbon composite coating and a tantalum carbide coating from inside to outside; wherein the thermal expansion coefficient of the pyrolytic carbon coating is 2.5-4.5 * 10 <-6 > / K, the thermal expansion coefficient of the composite coating is 4.5-6.0 * 10 <-6 > / K, and the thermal expansion coefficient of the tantalum carbide coating is 6.1-8.0 * 10 <-6 > / K. According to the gradient transition structure of the coating, the problem that thermal expansion coefficients between the coating and a base body are not matched is solved, the thermal shock resistance of the coating is effectively improved, meanwhile, the pinning effect can be achieved, the adhesive force between the coatings is enhanced, and the service life of a product is prolonged; compared with a single tantalum carbide coating, crack accumulation and through holes cannot be generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, and in particular to a gradient transition composite tantalum carbide coating and a preparation method thereof. Background Art

[0002] The growth of GaN or AlN single crystals by MOCVD equipment and the growth of SiC single crystals by PVT furnaces require not only sophisticated growth technology, but also high temperatures exceeding 2400°C and corrosive gas atmospheres, which place extremely high demands on the durability and purity of production equipment, especially key components such as trays and crucibles. The conventionally used graphite material is very easy to introduce trace impurities and cause contamination of the single crystal.

[0003] In order to solve this problem, a coating that can withstand high temperatures and avoid contamination must be applied to the surface of the graphite parts. Tantalum carbide (TaC), as an ultra-high temperature tantalum compound, has the advantages of high melting point, high hardness, and corrosion resistance. It can be used stably at high temperatures for a long time and can withstand corrosion from a variety of substances including hydrogen (H2), ammonia (NH3), silane (SiH4), and silicon (Si). It is an ideal coating material for graphite parts used in MOCVD preparation of GaN or AlN single crystals and PVT preparation of SiC single crystals. By using TaC coating, the quality and yield of single crystal production can be significantly improved.

[0004] Prior art CN115948721B discloses a method for preparing tantalum carbide coating by CVD method; it relates to the field of tantalum carbide coating preparation; the specific steps of the method are as follows: pre-treat the substrate material; place the pre-treated substrate material in the reaction chamber of the CVD furnace, start the vacuum pump, pump the pressure in the furnace to below 100Pa, stop the vacuum pump, fill argon, let it stand, start the vacuum pump again, pump the pressure in the furnace to below 30Pa; heat to reach the deposition temperature, and keep warm; start the evaporation device, set the temperature and pressure, sublimate the tantalum salt into a gaseous state, introduce argon as a carrier gas, carry the gaseous tantalum salt to a mixing tank, and mix it evenly with hydrogen and propylene; the mixed gas enters the CVD furnace, heats, controls the gas pressure, deposits, stops introducing gas, stops heating, cools, and obtains a tantalum carbide coating. The tantalum carbide coating prepared by the invention has high mechanical properties and excellent high temperature corrosion resistance and thermal shock resistance. However, since the thermal expansion coefficients of the graphite substrate and the coating of the method are very different, the relevant thermal expansion coefficient data are also listed in the invention, which may cause microcracks or cracks in the coating and affect the performance of the coating.

[0005] Prior art CN112374891A discloses a graphite base plate surface gradient TaC coating and its preparation method, including a graphite base plate substrate, the surface of the graphite base plate substrate is provided with a gradient TaC coating; the gradient TaC coating includes a TaC component and a C component, the content of the TaC component gradually increases from 0% to 100% from the inside to the outside, and the gradient distribution conforms to the y=ax linear equation law or conforms to the y=ax2 parabolic law distribution. The invention uses CVD dynamic co-deposition technology to achieve a gradient span of the TaC component content in the coating from 0-100%. Since the inner layer of the coating is a pyrolytic carbon layer, its thermal expansion coefficient is similar to that of the graphite substrate, and then gradually transitions, which can effectively improve the thermal matching difference between the coating and the substrate; at the same time, the soft C component structure and nanopores in the coating can effectively alleviate the thermal expansion of the TaC crystal to reduce the stress peak in the coating. However, the invention has the following problems: 1. Difficulty in controlling the composition: Multi-component co-deposition requires precise control of the flow rate and reaction conditions of different precursors to ensure uniform deposition of each component. However, the reactivity of different gases may be different, which makes it difficult to accurately control the proportion of components, affecting the uniformity and performance of the coating. 2. Complex process parameters: In order to obtain an ideal multi-component coating, it is necessary to accurately adjust a variety of process parameters, such as gas flow, temperature, pressure, etc. mentioned in the patent. The optimization process of these parameters is complex and time-consuming, which increases the difficulty and cost of the process. 3. There are mutual reactions and by-products: In a multi-component system, different precursors may react with each other undesirably to generate by-products (such as more free carbon or tantalum carbide, etc.). These by-products may contaminate the coating or form impurities on the surface of the substrate, affecting the performance and purity of the coating. 4. Multi-layer structures are difficult to control: In multi-component CVD co-deposition, it may be challenging to form multi-layer or gradient coatings. The thickness and composition uniformity of each layer need to be precisely controlled to achieve the desired performance, which places higher requirements on process design and control. 5. Repeatability and stability are difficult to guarantee: Since multi-component CVD co-deposition involves multiple precursors and complex reaction conditions, it is difficult to ensure the consistency and stability of each deposition process.

[0006] Therefore, it is necessary to provide a tantalum carbide coating preparation technology. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a gradient transition composite tantalum carbide coating and a preparation method thereof. The tantalum carbide composite coating includes a tantalum carbide coating from the surface to the inside, a tantalum carbide-pyrolytic carbon composite coating and a pyrolytic carbon coating; the present invention uses a high-temperature chemical vapor deposition method to prepare the entire gradient transition composite tantalum carbide coating at one time, which not only effectively enhances the adhesion between the coating and the substrate, but also alleviates the cracking problem caused by the difference in thermal expansion coefficient to a certain extent.

[0008] The technical solution of the present invention is:

[0009] A gradient transition composite tantalum carbide coating, which is located on the surface of a graphite substrate material, and includes, from inside to outside: a pyrolytic carbon coating, a tantalum carbide-pyrolytic carbon composite coating, and a tantalum carbide coating;

[0010] Among them, the thermal expansion coefficient of pyrolytic carbon coating is 2.5-4.5×10 -6 / K, thermal expansion coefficient of composite coating is 4.5-6.0×10 -6 / K, thermal expansion coefficient of tantalum carbide coating is 6.1-8.0×10 -6 / K.

[0011] Further, the thickness of the gradient transition composite tantalum carbide coating is 45 to 225 μm. Specifically, the thickness of the pyrolytic carbon coating is 20 to 100 μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 5 to 25 μm, and the thickness of the tantalum carbide coating is 20 to 100 μm.

[0012] The present invention also provides a method for preparing a gradient transition composite tantalum carbide coating, comprising the following steps:

[0013] (1) Pre-treating the substrate material: using an organic solvent to clean the surface of the graphite substrate material, and then removing the residual organic solvent on the surface;

[0014] (2) using a carrier gas to transport the carbon source gas into the reaction chamber, controlling the flow rate ratio of the carrier gas to the carbon source to be 1.2-1.4:0.8-1.0, and using a high temperature chemical vapor deposition method to deposit a pyrolytic carbon coating on the surface of the graphite substrate material;

[0015] (3) After the deposition is completed, the carbon source gas is stopped, the tantalum salt is heated to sublime, and then transported into the reaction chamber by a carrier gas, and the reducing gas is simultaneously transported into the reaction chamber by a carrier gas, and the flow ratio of the tantalum salt, the carrier gas and the reducing gas is 1.0-1.2:1.2-1.4:1, and a tantalum carbide-pyrolytic carbon composite coating is prepared by an in-situ reaction on the surface of the pyrolytic carbon;

[0016] (4) After the tantalum carbide-pyrolytic carbon composite coating is prepared, a carbon source gas is introduced, wherein the flow ratio of tantalum salt, carrier gas and reducing gas is 1.0-1.2:1.2-1.4:1, and the flow ratio of carrier gas to carbon source is 1.2-1.4:0.8-1.0, and a layer of tantalum carbide coating is deposited on the tantalum carbide-pyrolytic carbon composite coating by high temperature chemical vapor deposition;

[0017] (5) After the deposition is completed, stop introducing gas and allow to cool and clean naturally.

[0018] Furthermore, the temperature of chemical vapor deposition is 1600° C. to 2200° C., the heating rate to the deposition temperature is 5 to 20° C. / min, and the deposition time is 2 to 8 hours.

[0019] Furthermore, the flow rate of the carbon source in step (2) is 2.0 to 5.0 L / min.

[0020] Furthermore, in step (3), the flow rate of the reducing gas is 2.0 to 5.0 L / min.

[0021] Furthermore, the in-situ reaction temperature of step (3) is 1600°C to 2200°C, the pressure is 2000Pa-10000Pa, and the reaction time is 1-4h.

[0022] Furthermore, the carrier gas is argon, and the carbon source is one or two of methane, ethane, propane and propylene.

[0023] Another object of the present invention is to apply the gradient transition composite tantalum carbide coating in the field of preparing GaN or AlN single crystals by MOCVD and preparing SiC single crystals by PVT.

[0024] Another object of the present invention is to provide a carbon material, comprising a graphite substrate material and the gradient transition composite tantalum carbide coating of the present invention.

[0025] Compared with the prior art, the gradient transition composite tantalum carbide coating and the preparation method thereof provided by the present invention have the following advantages:

[0026] (1) The gradient transition structure of the gradient transition composite tantalum carbide coating of the present invention not only alleviates the problem of thermal expansion coefficient mismatch between the coating and the substrate, effectively improves the thermal shock resistance of the coating, but also plays a pinning role, enhances the adhesion between the coatings, and improves the service life of the product. Compared with a single tantalum carbide coating, no crack accumulation and through holes will be generated.

[0027] (2) The preparation process of the coating of the present invention is easy to control. The type of raw materials introduced during the deposition process is changed to deposit a pyrolytic carbon coating, a tantalum carbide-pyrolytic carbon composite coating and a tantalum carbide coating on the surface of the graphite substrate in sequence. The composite coating has a gradient transition structure and has the characteristic that the thermal expansion coefficient increases continuously from the graphite substrate to the outer coating material. It connects the previous and the next, effectively improves the thermal shock resistance of the coating, and at the same time enhances the bonding force between the coatings, so that the coating is not easy to peel off and cause failure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the structure of the gradient transition composite tantalum carbide coating of the present invention;

[0029] Figure 2 This is the appearance of the composite tantalum carbide coating of Example 3 of the present invention;

[0030] Figure 3 This is the XRD diagram of the coating of Example 3 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the protection scope of the present invention.

[0032] In the following examples and comparative examples, reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies. The methods used are all prior art unless otherwise specified.

[0033] Embodiment 1 A method for preparing a gradient transition composite tantalum carbide coating comprises the following steps:

[0034] (1) High-purity graphite was selected as the substrate material, which was placed in acetone for 20 min and then placed in ultrapure water for 20 min, and then dried in a vacuum oven.

[0035] (2) Place the pretreated graphite substrate in the CVD reaction chamber, turn on the mechanical pump, pump the chamber pressure to below 10Pa, turn on the molecular pump, and the pressure is less than 1×10 -3 Pa, turn off the molecular pump, and introduce argon as a carrier gas, pressurize to 500Pa, then heat the reaction chamber to 2200℃, and increase the heating rate to the deposition temperature at a rate of 5-20℃ / min. Ethane is transported into the reaction chamber using argon as a carrier gas, with an ethane flow rate of 2.0L / min and an argon flow rate of 3.5L / min. The pyrolytic carbon coating is obtained by deposition for 4h.

[0036] (3) After the deposition is completed, the introduction of ethane is stopped, and the inorganic tantalum salt (tantalum pentachloride) evaporation chamber is heated to 400°C, the tantalum salt is heated to sublime, and then transported into the reaction chamber through a carrier gas, and hydrogen is simultaneously introduced using argon as a carrier gas, wherein the tantalum salt flow rate is 3.2 L / min, the hydrogen flow rate is 2.9 L / min, and the argon flow rate is 3.5 L / min. An in-situ reaction is carried out on the pyrolytic carbon surface at 2000°C and a pressure of 2000 Pa. The reaction is carried out for 4 hours to obtain a tantalum carbide-pyrolytic carbon composite coating.

[0037] (4) After the preparation of the tantalum carbide-pyrolytic carbon composite coating, ethane was again transported to the reaction chamber using argon as a carrier gas, with a tantalum salt flow rate of 3.2 L / min, ethane flow rate of 2.0 L / min, hydrogen flow rate of 2.9 L / min, and argon flow rate of 3.5 L / min. High-temperature chemical vapor deposition was used to deposit at 2200°C (heating rate of 5-20°C / min) for 2 h to obtain a tantalum carbide coating.

[0038] (5) After the deposition is completed, turn off the heating power supply and wait for the vapor deposition equipment to cool down. When the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and introduce argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared gradient transition composite tantalum carbide coating consisting of three parts: pyrolytic carbon coating, tantalum carbide-pyrolytic carbon composite coating and tantalum carbide coating (refer to Figure 1 ) samples.

[0039] The thermal expansion coefficient of the pyrolytic carbon coating of the sample obtained in this example is 4.3×10 -6 / K, thermal expansion coefficient of composite coating is 5.4×10 -6 / K, thermal expansion coefficient of tantalum carbide coating is 6.2×10 -6 / K). The thickness of the sample gradient transition composite tantalum carbide coating is 84 μm, of which the thickness of the pyrolytic carbon coating is 36 μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 12 μm, and the thickness of the tantalum carbide coating is 36 μm.

[0040] Embodiment 2 A method for preparing a gradient transition composite tantalum carbide coating comprises the following steps:

[0041] (1) High-purity graphite was selected as the substrate material, which was placed in benzene for 20 min of ultrasonic treatment, then placed in ultrapure water for 20 min of ultrasonic treatment, and then dried in a vacuum oven.

[0042] (2) Place the pretreated graphite substrate in the CVD reaction chamber, turn on the mechanical pump, pump the chamber pressure to below 10Pa, turn on the molecular pump, and the pressure is less than 1×10 -3 Pa, turn off the molecular pump, and introduce argon as a carrier gas, pressurize to 500Pa, and then heat the reaction chamber to 1600℃; the heating rate to the deposition temperature is 5-20℃ / min, and propylene is transported to the reaction chamber with argon as a carrier gas, with a propylene flow rate of 4.0L / min and an argon flow rate of 5.6L / min. The pyrolytic carbon coating is obtained by deposition for 8h.

[0043] (3) After the deposition is completed, the introduction of propylene is stopped, and the inorganic tantalum salt (tantalum pentachloride) evaporation chamber is heated to 400° C. The tantalum salt is heated to sublime, and then transported into the reaction chamber through a carrier gas, and hydrogen is simultaneously introduced using argon as a carrier gas, wherein the tantalum salt flow rate is 4.8 L / min, the hydrogen flow rate is 4.0 L / min, and the argon flow rate is 5.6 L / min. An in-situ reaction is carried out on the pyrolytic carbon surface at 1800° C. and a pressure of 10000 Pa. The reaction is carried out for 1 hour to obtain a tantalum carbide-pyrolytic carbon composite coating.

[0044] (4) After the preparation of the tantalum carbide-pyrolytic carbon composite coating, propylene was again transported to the reaction chamber using argon as the carrier gas, with a tantalum salt flow rate of 4.8 L / min, a propylene flow rate of 4.0 L / min, a hydrogen flow rate of 4.0 L / min, and an argon flow rate of 5.6 L / min. A high-temperature chemical vapor deposition method was used to deposit at 1600°C for 8 hours to obtain a tantalum carbide coating.

[0045] (5) After the deposition is completed, turn off the heating power supply and wait for the vapor deposition equipment to cool down. When the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and introduce argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared gradient transition composite tantalum carbide coating consisting of three parts: pyrolytic carbon coating, tantalum carbide-pyrolytic carbon composite coating and tantalum carbide coating (refer to Figure 1 ) samples.

[0046] The thermal expansion coefficient of the pyrolytic carbon coating of the sample obtained in this example is 4.5×10 -6 / K, thermal expansion coefficient of composite coating is 5.1×10 -6 / K, thermal expansion coefficient of tantalum carbide coating is 6.6×10 -6 / K). The thickness of the sample gradient transition composite tantalum carbide coating is 125 μm, of which the thickness of the pyrolytic carbon coating is 50 μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 25 μm, and the thickness of the tantalum carbide coating is 50 μm.

[0047] Embodiment 3 A method for preparing a gradient transition composite tantalum carbide coating comprises the following steps:

[0048] (1) High-purity graphite was selected as the substrate material, which was placed in anhydrous ethanol for ultrasonic treatment for 20 min, then placed in ultrapure water for ultrasonic treatment for 20 min, and then dried in a vacuum oven.

[0049] (2) Place the pretreated graphite substrate in the CVD reaction chamber, turn on the mechanical pump, pump the chamber pressure to below 10Pa, turn on the molecular pump, and the pressure is less than 1×10 -3 Pa, turn off the molecular pump, and introduce argon as a carrier gas, pressurize to 500Pa, and then heat the reaction chamber to 2000℃; the heating rate to the deposition temperature is 5-20℃ / min, and methane is transported to the reaction chamber with argon as a carrier gas, with a methane flow rate of 4.0L / min and an argon flow rate of 6.3L / min. The pyrolytic carbon coating is obtained by deposition for 2h.

[0050] (3) After the deposition is completed, the introduction of methane is stopped, and the inorganic tantalum salt (tantalum pentachloride) evaporation chamber is heated to 400°C, the tantalum salt is heated to sublime, and then transported into the reaction chamber through a carrier gas, and hydrogen is introduced simultaneously using argon as a carrier gas, wherein the tantalum salt flow rate is 4.5 L / min, the hydrogen flow rate is 4.5 L / min, and the argon flow rate is 6.3 L / min. At 1600°C and a pressure of 4000 Pa, an in-situ reaction is carried out on the pyrolytic carbon surface for 3 hours to obtain a tantalum carbide-pyrolytic carbon composite coating.

[0051] (4) After the preparation of the tantalum carbide-pyrolytic carbon composite coating, methane was again transported to the reaction chamber using argon as a carrier gas, with a tantalum salt flow rate of 4.5 L / min, a methane flow rate of 4.0 L / min, a hydrogen flow rate of 4.5 L / min, and an argon flow rate of 6.3 L / min. A high-temperature chemical vapor deposition method was used to deposit at 2000°C for 4 hours to obtain a tantalum carbide coating.

[0052] (5) After the deposition is completed, turn off the heating power supply and wait for the vapor deposition equipment to cool down. When the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and introduce argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared gradient transition composite tantalum carbide coating consisting of three parts: pyrolytic carbon coating, tantalum carbide-pyrolytic carbon composite coating and tantalum carbide coating (refer to Figure 1 Samples (see Figure 2 shown).

[0053] The thermal expansion coefficient of the pyrolytic carbon coating of the sample obtained in this example is 4.0×10 -6 / K, thermal expansion coefficient of composite coating is 5.5×10 -6 / K, thermal expansion coefficient of tantalum carbide coating is 6.1×10 -6 / K). The thickness of the sample gradient transition composite tantalum carbide coating is 55μm, of which the thickness of the pyrolytic carbon coating is 25μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 5μm, and the thickness of the tantalum carbide coating is 25μm. XRD detection of the sample is as follows Figure 3 shown.

[0054] Comparative Example 1: A method for preparing a gradient transition composite tantalum carbide coating, comprising the following steps:

[0055] (1) High-purity graphite was selected as the substrate material, which was placed in anhydrous ethanol for ultrasonic treatment for 20 min, then placed in ultrapure water for ultrasonic treatment for 20 min, and then dried in a vacuum oven.

[0056] (2) The pretreated graphite substrate was placed in a CVD reaction chamber, and the temperature of the reaction chamber was raised to 2000°C; the inorganic tantalum salt evaporation chamber was directly heated to 400°C, the tantalum salt was heated to sublime, and then transported into the reaction chamber through a carrier gas, and hydrogen and methane were simultaneously introduced using argon as a carrier gas, wherein the tantalum salt flow rate was 4.5 L / min, the methane flow rate was 4.0 L / min, the hydrogen flow rate was 4.5 L / min, and the argon flow rate was 6.3 L / min. A high-temperature chemical vapor deposition method was used to deposit at 2000°C for 4 hours to obtain a tantalum carbide coating sample.

[0057] The obtained sample is different from Example 3 in that the TaC coating (the thermal expansion coefficient of the tantalum carbide coating is 6.1×10 -6 / K), after deposition, the coating cracks due to the difference in thermal expansion coefficient.

[0058] Comparative Example 2:

[0059] Compared with Example 3, the difference is that the deposition temperature is 1400° C. Other matters are the same as those in Example 3.

[0060] Result: After deposition, no completely wrapped coating was formed and the graphite substrate was still exposed.

[0061] Comparative Example 3:

[0062] Compared with Example 3, the difference is that the deposition temperature is 2300° C., and other matters are the same as Example 3.

[0063] Results: The coating generated after deposition was black. XRD detection revealed that there was a large amount of free carbon in the coating. The reason was that the temperature was too high and the methane decomposed violently, resulting in the presence of free carbon in the coating.

[0064] Comparative Example 4:

[0065] Compared with Example 3, the difference is that the pyrolytic carbon deposition time is 1 hour, the transition coating preparation time is 0.5 hours, the tantalum carbide coating deposition time is 1 hour, and the total deposition time is 2.5 hours. Other matters are the same as in Example 3.

[0066] Results: The thickness of the gradient transition composite tantalum carbide coating after deposition was 22 μm, of which the thickness of the pyrolytic carbon coating was 10 μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating was 2 μm, and the thickness of the tantalum carbide coating was 10 μm. If the coating thickness is too small, it cannot provide sufficient protection, which may cause the graphite substrate to be exposed to the environment, increasing the risk of corrosion, wear or other damage. At the same time, the durability is low, and it is easy to be worn or damaged in long-term use, reducing the overall life and performance of the coating.

[0067] Comparative Example 5:

[0068] Compared with Example 3, the difference is that the pyrolytic carbon deposition time is 10 hours, the transition coating preparation time is 6 hours, the tantalum carbide coating deposition time is 10 hours, and the total deposition time is 26 hours. Other matters are the same as Example 3.

[0069] Results: After deposition, the thickness of the gradient transition composite tantalum carbide coating is 250μm, of which the thickness of the pyrolytic carbon coating is 110μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 30μm, and the thickness of the tantalum carbide coating is 110μm. Too thick a coating will increase the overall weight of the sample and cause the key dimensions of the product to exceed the standard.

[0070] Comparative Example 6:

[0071] Compared with Example 3, the difference is that the deposition temperature is 1400° C., the pyrolytic carbon deposition time is 1 hour, the transition coating preparation time is 0.5 hour, the tantalum carbide coating deposition time is 1 hour, and the total deposition time is 2.5 hours. Other matters are the same as Example 3.

[0072] Result: After deposition, no completely wrapped coating was formed and the graphite substrate was still exposed.

[0073] Comparative Example 7:

[0074] Compared with Example 3, the difference is that the tantalum salt carrier gas argon flow rate is 3.5 L / min, the methane flow rate is 6.5 L / min, the hydrogen flow rate is 2.0 L / min, and the argon flow rate is 3.5 L / min. Other matters are the same as in Example 3.

[0075] Test Example The coating samples obtained in Examples 1-3 and Comparative Examples 1-7 were respectively subjected to the following tests:

[0076] (1) Thickness test

[0077] SEM test was performed on the cross section of the product.

[0078] (2) Strength test

[0079] Method: Using the cross method, two rectangular strips of the same shape and size are bonded together in a cross form. The interface stretching can be obtained by applying a load to the cross pattern.

[0080] (3) Thermal shock resistance test

[0081] Method: Place the sample in a muffle furnace for a temperature test. Heat it to 800°C and keep it warm for 15 minutes. Then take it out and quickly put it in water at 20°C-25°C for rapid cooling. Repeat the above operation and record the number of times cracks first appear on the coating surface or the number of times the coating first peels off. Take the average value of three samples for each data.

[0082] The sample test results are shown in Tables 1 and 2.

[0083] Table 1 Test data of samples obtained in Examples 1-3

[0084]

[0085] It can be seen from the data in Table 1 that the porous structure of the pyrolytic carbon-carbon coating of the coating sample obtained in the embodiment of the present invention can not only improve the surface defects of the graphite substrate, but also an in-situ reaction will occur between the tantalum salt and the pyrolytic carbon coating to generate a C-TaC layer structure. The gradient transition structure of substrate-pyrolytic carbon-composite coating-tantalum carbide coating not only alleviates the problem of thermal expansion coefficient mismatch between the coating and the substrate, effectively improves the thermal shock resistance of the coating, but also plays a pinning role: the prepared pyrolytic carbon coating is a porous structure. During the preparation of the composite coating, the tantalum salt will penetrate into the pores and react with the pyrolytic carbon in situ to generate a tantalum carbide composite coating. The transition coating formed is like nails nailed to each other, and has a stronger bonding force. The tantalum carbide composite coating of the present invention can be applied to semiconductor crystal growth. Crystal growth and epitaxy are two processes required in the semiconductor manufacturing industry. The temperature required for crystal growth exceeds 2400°C, while the temperature required for epitaxy is only below 1500°C, and the melting point of silicon carbide is much lower than 2400°C.

[0086] Table 2 Test data of samples obtained from Example 3 and Comparative Examples 1-7

[0087]

[0088]

[0089] From the data in Table 2, it can be seen that in Comparative Example 1, the sample obtained directly deposited TaC coating on the graphite substrate (the thermal expansion coefficient of tantalum carbide coating was 6.1×10 -6 / K), after deposition, the coating cracks due to the difference in thermal expansion coefficient.

[0090] In Comparative Example 2, no completely wrapped coating was generated after deposition, and the graphite substrate was still exposed.

[0091] The coating generated after deposition in Comparative Example 3 is black. XRD detection shows that a large amount of free carbon exists in the coating. The reason is that the temperature is too high and the methane decomposes violently, resulting in the presence of free carbon in the coating.

[0092] Comparative Example 4 has a gradient transition composite tantalum carbide coating thickness of 22 μm after deposition, of which the pyrolytic carbon coating thickness is 10 μm, the tantalum carbide-pyrolytic carbon composite coating thickness is 2 μm, and the tantalum carbide coating thickness is 10 μm. The coating thickness is too small to provide adequate protection, which can easily lead to the graphite substrate being exposed to the environment, increasing the risk of corrosion, wear or other damage. At the same time, the durability is low, and it is easy to be worn or damaged in long-term use, reducing the overall life and performance of the coating.

[0093] Comparative Example 5 has a gradient transition composite tantalum carbide coating thickness of 250 μm after deposition, of which the pyrolytic carbon coating thickness is 110 μm, the tantalum carbide-pyrolytic carbon composite coating thickness is 30 μm, and the tantalum carbide coating thickness is 110 μm. Too thick a coating thickness will increase the overall weight of the sample and cause the key dimensions of the product to exceed the standard.

[0094] Comparative Example 6 did not generate a completely wrapped coating after deposition, and the graphite substrate was still exposed.

[0095] The coating generated after deposition in Comparative Example 7 is black. XRD detection shows that the main component of the coating is C, and it contains only a small amount of TaC, and has no protective effect.

[0096] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A gradient transition composite tantalum carbide coating, characterized in that: The gradient transition composite tantalum carbide coating is located on the surface of the graphite substrate material, and from the inside to the outside, it is: a pyrolytic carbon coating, a tantalum carbide-pyrolytic carbon composite coating and a tantalum carbide coating; Among them, the thermal expansion coefficient of pyrolytic carbon coating is 2.5-4.5×10 -6 / K, thermal expansion coefficient of composite coating is 4.5-6.0×10 -6 / K, thermal expansion coefficient of tantalum carbide coating is 6.1-8.0×10 -6 / K.

2. The gradient transition composite tantalum carbide coating according to claim 1, characterized in that: The thickness of the gradient transition composite tantalum carbide coating is 45 to 225 μm. Specifically, the thickness of the pyrolytic carbon coating is 20 to 100 μm, the thickness of the tantalum carbide-pyrolytic carbon composite coating is 5 to 25 μm, and the thickness of the tantalum carbide coating is 20 to 100 μm.

3. A method for preparing a gradient transition composite tantalum carbide coating, characterized in that: The following steps are involved: (1) Pre-treating the substrate material: using an organic solvent to clean the surface of the graphite substrate material, and then removing the residual organic solvent on the surface; (2) using a carrier gas to transport the carbon source gas into the reaction chamber, controlling the flow rate ratio of the carrier gas to the carbon source to be 1.2-1.4:0.8-1.0, and using a high temperature chemical vapor deposition method to deposit a pyrolytic carbon coating on the surface of the graphite substrate material; (3) After the deposition is completed, the carbon source gas is stopped, the tantalum salt is heated to sublime, and then transported into the reaction chamber by a carrier gas, and the reducing gas is simultaneously transported into the reaction chamber by a carrier gas, and the flow ratio of the tantalum salt, the carrier gas and the reducing gas is 1.0-1.2:1.2-1.4:1, and a tantalum carbide-pyrolytic carbon composite coating is prepared by an in-situ reaction on the surface of the pyrolytic carbon; (4) After the tantalum carbide-pyrolytic carbon composite coating is prepared, a carbon source gas is introduced, wherein the flow ratio of tantalum salt, carrier gas and reducing gas is 1.0-1.2:1.2-1.4:1, and the flow ratio of carrier gas to carbon source is 1.2-1.4:0.8-1.0, and a layer of tantalum carbide coating is deposited on the tantalum carbide-pyrolytic carbon composite coating by high temperature chemical vapor deposition; (5) After the deposition is completed, stop introducing gas and allow to cool and clean naturally.

4. The method for preparing the gradient transition composite tantalum carbide coating according to claim 3, characterized in that: The temperature of chemical vapor deposition is 1600° C. to 2200° C., the heating rate to the deposition temperature is 5 to 20° C. / min, and the deposition time is 2 to 8 hours.

5. The method for preparing the gradient transition composite tantalum carbide coating according to claim 3, characterized in that: The flow rate of the carbon source in step (2) is 2.0 to 5.0 L / min.

6. The method for preparing the gradient transition composite tantalum carbide coating according to claim 3, characterized in that: The flow rate of the reducing gas in step (3) is 2.0 to 5.0 L / min.

7. The method for preparing the gradient transition composite tantalum carbide coating according to claim 3, characterized in that: The in-situ reaction temperature of step (3) is 1600° C. to 2200° C., the pressure is 2000 Pa to 10000 Pa, and the reaction time is 1 to 4 hours.

8. The method for preparing the gradient transition composite tantalum carbide coating according to claim 3, characterized in that: The carrier gas is argon, and the carbon source is one or two of methane, ethane, propane and propylene.

9. Application of the gradient transition composite tantalum carbide coating according to any one of claims 1 to 2 in the field of preparing GaN or AlN single crystals by MOCVD and preparing SiC single crystals by PVT.

10. A carbon material, characterized in that: It comprises a graphite substrate material and the gradient transition composite tantalum carbide coating as described in any one of claims 1-2.

Citation Information

Patent Citations

  • Graphite base disc surface gradient TaC coating and preparation method thereof

    CN112374891A

  • A method for preparing tantalum carbide coatings by CVD

    CN115948721B

Cited By

  • Composite current collector and preparation method thereof, battery, battery module and electric equipment

    CN120432547A

  • Composite current collector, preparation method thereof, battery, battery module and electric device

    CN120432547B

  • TaC composite coating process based on carbon nanostructure transition layer and product thereof

    CN120945342A

  • A process for producing a ta c composite coating based on a carbon nanostructure transition layer and the product thereof

    CN120945342B

  • Battery monomer and preparation method thereof, battery device and power utilization device

    CN122393508A